Mechanical properties of bitumen quenched dual phase steel - Amuda, M.O.H.; Olaniyan, T.A.; Osoba, L.O.; Akinlabi, E.T. (Penerbit Universiti Kebangsaan Malaysia, 2017)
The mechanical properties of Dual Phase Steel (DPS)-duplex structure-produced by quenching in pre-heated bitumen have been investigated. Medium carbon steels intercritically heated at different temperatures and holding times were quenched in hot bitumen. Optical and scanning electron microscopy characterisation of the duplex structure showed extensive network of fibrous martensite in a ferritic matrix with occasional presence of polygonal martensite. The duplex phase structure exhibited continuous yielding dynamics, improving the tensile and hardness values by about 42 and 35%, respectively, relative to the normalised structure. But, the elongation and impact values decreased by about 42 and 50%, respectively, when compared to the normalised structure. These values are similar to those obtained in duplex structure produced using conventional oil quenching. The tensile fractured surface showed transition between a predominantly cleavage mode in the lower annealing temperature to a mixed mode in the upper bound of the annealing temperature. These findings suggest that pre-heated bitumen can be exploited for the production of DPSs.